Soil pH Determines the Spatial Distribution, Assembly Processes, and Co-existence Networks of Microeukaryotic Community in Wheat Fields of the North China Plain - Shi, Yu; Xu, Mengwei; Zhao, Yige; Cheng, Liang; Chu, Haiyan (Frontiers in Microbiology, 2022)
Soil microeukaryotes play a pivotal role in soil nutrient cycling and crop growth in agroecosystems. However, knowledge of microeukaryotic community distribution patterns, assembly processes and co-existence networks is greatly limited. Here, microbial eukaryotes in bulk and rhizosphere soils of the North China Plain were investigated. The results showed that soil pH was the driving factor for the microeukaryotic community composition in the bulk and rhizosphere soils. The soil microeukaryotic community could significantly differ between alkaline and acidic soils. The results indicated that the soil pH had a stronger effect than niche differences on community composition. Partial Mantel tests showed that soil pH and spatial distance had similar effects on the microeukaryotic community composition in the bulk soil. However, in the rhizosphere soil, spatial distance had a stronger effect than soil pH. Infer Community Assembly Mechanisms by Phylogenetic bin-based null model (iCAMP) analysis revealed that drift was the most important process driving microeukaryotic community assembly, with an average relative importance of 37.4%–71.1%. Dispersal limitation displayed slightly greater importance in alkaline rhizosphere than in alkaline bulk soils. Meanwhile, the opposite trend was observed in acidic soils. In addition, the contribution of each assembly process to each iCAMP lineage “bin” varied according to the acidic or alkaline conditions of the soil and the niche environment. High proportions of positive links were found within the four ecological networks. Alkaline soil networks, especially the alkaline bulk soil network, showed greater complexity than the acidic soil networks. Natural connectivity analysis revealed that the rhizosphere community had a greater stability than the bulk soil community in alkaline soil. This study provides a foundation for understanding the potential roles of microbial eukaryotes in agricultural soil ecosystem functioning.